2018
DOI: 10.20473/jkr.v3i1.7455
|View full text |Cite
|
Sign up to set email alerts
|

RNA Isolation of Dengue Virus Type 2 with Different Precipitation Solvents : Methanol, Chloroform, and 2-Isopropanol.

Abstract: Dengue virus distributed in tropical and subtropical regions in the world. DENV viruses are transmitted between humans primarily by Aedes aegypti and Aedes albopictus mosquitoes and are endemic in most areas in which the vectors occur. Four serotypes of dengue virus are DENV-1, DENV-2, DENV-3 and DENV-4. DENV-2 is comprised of six genotypes. Ethanol precipitation is a commonly used technique for concentrating and de-salting nucleic acids (DNA or RNA) preparations in aqueous solution. RNA isolation by combining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…However, considering that these are environmental samples in which a large amount of targeted viral RNA was not expected, potential improvement of RNA isolation with the implementation of the formal, original protocol (O) set by the manufacturer was additionally tested with an alternative modified protocol (M). Untoro et al ( 29 ) conducted a similar study where they compared methanol, chloroform, and 2-isopropanol as alternative solvents to ethanol in the isolation of dengue virus type 2 RNA, and concluded that the used methanol and 2-isopropanol gave better results than ethanol. Generally speaking, the processing of environmental samples leads to a specific problem.…”
Section: Resultsmentioning
confidence: 99%
“…However, considering that these are environmental samples in which a large amount of targeted viral RNA was not expected, potential improvement of RNA isolation with the implementation of the formal, original protocol (O) set by the manufacturer was additionally tested with an alternative modified protocol (M). Untoro et al ( 29 ) conducted a similar study where they compared methanol, chloroform, and 2-isopropanol as alternative solvents to ethanol in the isolation of dengue virus type 2 RNA, and concluded that the used methanol and 2-isopropanol gave better results than ethanol. Generally speaking, the processing of environmental samples leads to a specific problem.…”
Section: Resultsmentioning
confidence: 99%
“…In this report, we have described (Untoro et al, 2018), DMSO, ethanol 96%, and acetone (Maharani et al, 2018 to A280. Pure RNA isolate has an A260/A280 ratio of 1.8 -2.1 (Farrel., 2005).…”
Section: Resultsmentioning
confidence: 99%